PERANCANGAN SISTEM INFORMASI MANAJEMEN BERBASIS SEKOLAH SMA NEGERI 1 MUARA BUNGO - Muhammad Hakiki; Radinal Fadli; Yogi Irdes Putra; Intan Putri Pertiwi (Jurnal Muara Pendidikan, 2021)
The development of information technology which is so fast and fast has brought the world into progress that is faster than previously imagined. The development of technology in the field of information by accessing the internet from anywhere and anytime. Internet technology is no longer a foreign sentence. The word website has become commonplace, because most of its function is to convey information from various parts of the world. One of the uses of IT as a form of information system is school management. The system designed is a school-based management information system at SMA N 1 Muara Bungo. The system designed is a school-based management information system at SMA N 1 Muara Bungo. This system design uses system analysis method, data analysis, system design using Data Flow Diagram (DFD) modeling language. Program coding using the Hypertext Processor (PHP) programming language. And the right data storage using MySQL. The design phase ended with program testing so as to create a School-based Management Information System for SMA N 1 Muara Bungo Using the Web. The system created can produce information in the form (schedules, modules, and class management) which can be accessed on the website.